Zniewolony umysł – zmiana biegunów recepcji - Dariusz Pawelec (Postscriptum Polonistyczne)
This article presents the changes through history in the reception of The Captive Mind by Czesław Miłosz. The book was published in 1953, first of all for the foreign readers. There were editions in English, French, German, Italian, Spanish, Swedish. However, it mainly evoked emotions of Poles at home and on emigration. After the 1989, with the first legal mass edition, we observed a decrease of interest in Poland for the Miłosz’s text. It has become a classical work, it kept up didactic function. On the other hand, the world response argues, through universal interpretations and new translations in 21th century (a Belorussian, Russian, Turkish, Catalan, Serbian), that the Miłosz’s propositions are current and attractive outside Poland, in other geopolitical conditions.